Covid-19 Sebagai Bentuk Overmacht dan Akibat Hukumnya Terhadap Pelaksanaan Perjanjian Kredit - Merry Tjoanda; Yosia Hetharie; Marselo Valentino Geovani Pariela; Ronald Fadly Sopamena (SASI, 2021)
The study is aimed at identifying and analyzing covid-19 as a form of relative overmacht and as a result of the overmacht law in the credit agreement and the policy of ending the credit agreement as a result of the covid-19 pandemic. The study method used in this study was normatif juridical, a doctrinal law study method by examining and studying the regulations of legislation that served asa basis for then analyzing the issues discussed. The study is analytical by using primary and secondary legal materials through the study of related documents and literature. The analysis used in the study is qualitative analysis to address the issues discussed. According to research, the covid-19 is a non-natural disaster that can therefore be categorized as overmacht measurement. As a form of overmacht relative, the result of the law of the spread of covid-19 as the overmacht relative to the credit agreement is that the debtor still has to fulfill his obligations to the debtor after the covid-19 is over. In its implementation based on POJK 11/2020, the debtor is given credit relief through restructuring in accordance with the form of restructuring issued by the bank in the form of lowering interest rates, extension of term, reduction of principal arrears, reduction of interest arrears and other forms according to verification and analysis of the bank on affected debtors covid-19.